Significance Of Specialized Subjects And Problem-Solving In Teaching Terms - Burkhanova Guzal Mukhammadievna; Ashirmatova Manzura Jumanboevna (Zien Journals, 2024)
This scientific article reveals the importance of specialized subjects and the solution of problems in teaching terms. Necessary issues related to the history, leading environment and trends of terms are directly related to the study of the most important and complex problems and teachings of modern linguistics - language education, which serves as linguistics.
Keywords: terminology; specialist subjects; solutions